Germenectomy of third molars with predictive cephalometry of abnormal eruption - Liuba González Espangler; Denia Morales Navarro; Lázaro Ibrahim Romero García (Editorial Ciencias Médicas, 2023)
Introduction: Complications associated with the abnormal eruption of third molars can be avoided with germenectomy of these teeth. Objective: To characterize the evolution of third molar germenectomy in patients with a cephalometric diagnosis of abnormal bud. Methods: An observational, descriptive and cross-sectional study was carried out in the Maxillofacial Surgery Service at Saturnino Lora Torres Provincial Hospital, from February 2019 to March 2021. Thirty two patients aged 13 to 15 years were studied, with 78 third molars undergoing surgery. The variables were age, sex, skin color, location and position of the third molar; as well as trans and postoperative complications and evolution. Results: Among the 32 patients included in the study, the female sex (62.5%) and the age of 14 years (40.6%) predominated. Complications that occurred during germenectomy were more frequent in the lower arch. Although no statistically significant differences were perceived according to location (p value > 0.05); with 30 intraoperative for 38.4% and 75 postoperative for 96.2%. Conclusions: There is evidence of a markedly favorable evolution after germenectomy of third molars in the population of patients with cephalometric diagnosis of abnormal bud. In them, transoperative bleeding and postoperative pain are the complications to consider in this type of surgical procedure.